The Environmental Performance of a Remote-Region Health Clinic Building, Australia, Based on Instrumental Monitoring. (June 2019) - Burroughs, S
Abstract: Both environmental (e.g., energy use) and human sustainability (occupant wellbeing/productivity) need to be considered in building design and operation. The challenging climatic and socioeconomic conditions in remote regions of Australia mean that achieving sustainability is difficult and costly. Currently, the energy use patterns, thermal performance, and indoor atmospheric quality (IAQ) of remote health clinic buildings are unknown, meaning that there is an information gap in the design and operation of such buildings. This paper reports the results of an investigation into the environmental performance of a clinic in the remote clinic of Numbulwar. Climate variables, energy consumption, and IAQ variables were instrumentally monitored at the clinic from April 2017 to March 2018 at 10-minute intervals, with data uploaded to a cloud database now holding 3 million values. Analyzed temporal variations in the measured variables for the clinic and the relationships between them reveal the performance of the building. The results obtained provide a basis for the formulation of strategic interventions, design guidance, and further investigation, including: (i) the range of indoor atmospheric conditions needs to be narrowed to provide more consistent occupant comfort; (ii) an occupancy profile needs to be developed to determine user behaviours with respect to energy use; (iii) the heat-exhaust/aircon systems need to be reviewed for more efficient use; (iv) the cycling of air, heat, moisture, and pollutants through the building needs to be further investigated; and (v) BIM should be undertaken using the data as input to test future design solutions.